Post-COVID-19 modular building review on problem-seeking framework: function, form, economy, and time. Issue 4 (23rd June 2022) - Hwang, Kyung-Eun; Kim, Inhan
Abstract: Modular building is an innovative and sustainable construction method and a notable architectural, engineering, and construction trend. Owing to the new constructability and sustainability, significant research efforts have been focused on the engineering aspects of modular building. Since the global outbreak of the COVID-19 pandemic, space utilization has changed radically, and a rethinking of modular building design has become essential. However, current literature lacks a comprehensive understanding of occupants' newly developed requirements and the relevant changes associated with engineering developments. Therefore, this study aims to review the current status of residential modular building design and construction, define its problems, and identify the key factors necessary for modular design and construction during the post-COVID-19 period from the perspective of architectural design. A total of 220 articles were selected from the Scopus database, out of which 94 papers were selected for a systematic review. The findings indicate that the present academic research primarily focuses on the technical aspects of optimizing architecture and on modularized plans to facilitate cost-effective factory production. Modular residential design has rarely considered people and cultural factors. Therefore, the authors derived 15 problems by adapting four architectural programming frameworks; function, form, economy, and time. The identified problems are mapped for future development with 11 problem-solving proposals. The proposed method contributes to developing new insights into COVID-19's impacts on dwelling environments and can help introduce modular residential design responses that enhance the quality of life by creating better residentials in the post-pandemic. Graphical Abstract: